Adoption of business analytics and impact on performance: a qualitative study in retail. Issue 11 (10th September 2017) - Ramanathan, Ramakrishnan; Philpott, Elly; Duan, Yanqing; Cao, Guangming
Abstract: This paper describes a qualitative study aimed at understanding issues faced by retail firms when they start a project of implementing business analytics (BA) and understanding the impact of BA implementation on business performance. Our study is informed by prior literature and the theoretical perspectives of the Technology–Organisation–Environment (TOE) framework but is not constrained by this theory. Using case studies of nine retailers in the U.K, we have found support for the link between TOE elements and adoption. In addition, we have identified more interesting involvement of additional factors in ensuring how firms could maximise benefit derived from BA and traditional TOE factors that potentially could have additional impacts different from the ones. For example, there appears a link between adoption of BA and business performance (including performance in terms of environmental sustainability), and this link is moderated by the level of BA adoption, IT integration and trust.